Successful laparoscopic trans-peritoneal repair of an incisional inguinal hernia, resulting from deep lymph node dissection for melanoma: A case report. (2020) - Clementi, M.; Di Furia, M.; Sista, F.; Mackay, A.R.; Guadagni, S.
Highlights: Groin incisional hernia may result like late complication of deep pelvic dissection. When this type of inguinal ventral hernia develops, the surgeon is facing some problems different to the common ventral hernia repair. Most of these difficulties may be overcome using laparoscopic approach. We present a case of successful laparoscopic repair of a giant ventral hernia developed like late complication of deep pelvic dissection for melanoma. To our knowledge, no other laparoscopic repair of this type of ventral hernia has been previously reported. Abstract: Introduction: Deep pelvic lymph node dissection for cancer may result in incisional inguinal hernias. We present a case report of successful laparoscopic trans-peritoneal repair of a large ventral inguinal hernia that developed following ileo-inguinal lymph node dissection (CLND) for melanoma. Case presentation: A successful 3 port laparoscopic trans-peritoneal procedure was performed on a 56-year-old female for the repair of a left inguinal hernia, developed 13 months following CLND for melanoma. The large oval 18 × 14 cm inguinal defect, with superior margins bordering the conjoint tendon and inferior margins bordering the ileo-psoas muscle, femoral vessels and nerve, was not closed in order to avoid excessive tension and was repaired by fixing a 25 × 20 cm intra-peritoneal mesh to abdominal borders at superior and lateral margins with permanent fasteners and at the inferior margin by a cyanoacrylate-glued overlap to protect femoral vessels and nerves from damage. No hernia recurrence was observed 8 months following this procedure. Discussion: Incisional inguinal hernias, following CLND, are rare but present a challenge to surgeons due to the difficulty in identifying both anatomical plains and safe sites for stable repair. Conclusions: We report a laparoscopic trans-peritoneal approach for the safe, reproducible and efficacious repair of incisional inguinal hernias that result from CLND. In our opinion prevention of hernia recurrence can be achieved by a intraperitoneal large mesh fixed at superior and lateral margin borders with permanent fasteners and using cyanoacrylate glue to overlap inferior margin borders in order to prevent vessels and/or nerve injury.